THE STUDY OF SIZE EFFECTS ON MECHANICAL PROPERTIES AND DEFECTS EVOLUTION IN NANO ALUMINUM BASED ON MOLECULAR DYNAMICS SIMULATION - WANG LuSheng; DING Jun; SONG Kun; LIU Bo; HUANG Xia (Jixie qiangdu)
The size effects on the mechanical properties and defect evolution process of single crystal aluminum with a center crack under tensile loading have been simulated through molecular dynamic method. With the increase of model size, the yield stress and yield point decreased, while the fracture toughness increased. In the elastic stage, the deformation relies heavily on the point defects and surface defects in materials, while in plastic stage it depends strongly on the dislocation multiplication and its slip. The stress concentration at the crack tip is mainly associated with the phase transformation of the crystal structure near the crack tip due to the stress relaxation after phase transformation.